CORRUPTION IN NIGERIA: A CHALLENGE TO SUSTAINABLE DEVELOPMENT IN THE FOURTH REPUBLIC - Mohammed, Usman (European Scientific Journal, ESJ, 2013)
The United Nations Global programme against corruption (UNGPAC) defines it as â€œabuse of power for private gainâ€. The paper examines corruption as a challenge to sustainable development in the fourth republic. In this research work, attempt was made to conceptualize corruption and sustainable development .With regards to the methodology, the paper was based on systematic qualitative content analysis .We also used historical and cultural theory of corruption as the tool of our analysis. A cursory observation into the Fourth Republic in Nigeria reveals that corruption was perpetrated with impunity with little or no effort at bringing the perpetrators to justice. Despite the establishment of the anti-graft commissions by the Obasanjo Administration, corruption has continued to escalate like wildfire. Therefore, this paper attempts to extrapolate the factors that were responsible for this high profile corrupt practices in Nigeria and this were traceable to historical and cultural factors of the components that make up the country. The amalgamation of Nigeria in 1914 by Sir Frederick Lugard placed the three major ethnic groups in the country advantaged over the minority ethnic groups. The minorities, who felt insecure in the hands of the major ethnic groups therefore, resorted to manipulations just as the major ethnic groups attempt to maneuver their ways. It is this suspicious attitude of the people that make up the country for one another, and for what a person in position is likely to be, that results in corrupt practices. It is therefore, the contention of this paper that unless this phenomenon is fought with every decorum it deserves by the Federal government of Nigeria, sustainable development will be a mirage with dare consequences on the economy, the citizenry and on our collective image globally. The anti-graft commissions should therefore be empowered to work assiduously without being molested or interfered with by the government. The paper contended that unless good governance is in place with accountability carefully observed, sustainable development cannot be realized.